Phase Ib/II trial testing combined radiofrequency ablation and ipilimumab in uveal melanoma (SECIRA-UM). Issue 3 (June 2020) - Rozeman, Elisa A.; Prevoo, Warner; Meier, Mark A.J.; Sikorska, Karolina; Van, Trieu M.; van de Wiel, Bart A.; van der Wal, Jacqueline E.; Mallo, Henk A.; Grijpink-Ongering, Lindsay G.; Broeks, Annegien; Lalezari, Ferry; Reeves, Jason; et al.
Abstract : Approximately, 50% of patients with uveal melanoma develop distant metastasis for which no standard therapy is established. In contrast to cutaneous melanoma, the anti-CTLA-4 antibody ipilimumab showed no clinical activity in uveal melanoma. Liver directed therapies improve local control, but fail to show overall survival (OS) benefit. Preclinical experiments demonstrated that radiofrequency ablation (RFA) induced durable responses in combination with anti-CTLA-4. The aim of this phase Ib/II study was to assess safety and efficacy of RFA plus ipilimumab in uveal melanoma. Patients underwent RFA of one liver lesion and subsequently received four courses ipilimumab 0.3, 3 or 10 mg/kg every 3 weeks in a 3 + 3 design. Primary endpoints were safety in terms of dose limiting toxicities per cohort to define the recommended phase II dose (RP2D) in the phase Ib part and confirmed the objective response rate and disease control rate (DCR) of non-RFA lesions in the phase II part. Secondary endpoints were progression-free survival (PFS) and OS. Ipilimumab 10 mg/kg + RFA was initially defined as the RP2D. However, after 19 patients, the study was amended to adjust the RP2D to ipilimumab 3 mg/kg + RFA, because 47% of patients treated with 10 mg/kg had developed grade 3 colitis. In the 3 mg/kg cohort, also 19 patients have been treated. Immunotherapy-related grade ≥3 adverse events were observed in 53% of patients in the 10 mg/kg cohort versus 32% in the 3 mg/kg cohort. No confirmed objective responses were observed; the confirmed DCR was 5% in the 10 mg/kg cohort and 11% in the 3 mg/kg cohort. Median PFS was 3 months and comparable for both cohorts, median OS was 14.2 months for the 10 mg/kg cohort versus 9.7 months for the 3 mg/kg cohort. Combining RFA with ipilimumab 3 mg/kg was well tolerated, but showed very limited clinical activity in uveal melanoma. Abstract : Supplemental Digital Content is available in the text.